2002
DOI: 10.1093/ajcn/76.3.504
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of vaccenic acid to conjugated linoleic acid in humans

Abstract: The results quantify the desaturation of VA to RA in humans. Conversion is likely to contribute significantly to the amount of RA available to the body, and dietary intakes of VA should thus be taken into account when predicting RA status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
284
1
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(300 citation statements)
references
References 36 publications
6
284
1
9
Order By: Relevance
“…Recent studies [10] have found that most of the RA in ruminant milk fat is synthesized endogenously from 11-trans C18:1 by desaturases. Furthermore, TVA has also been found as an RA precursor in human tissues [28]. If this evidence were confirmed, remarkable benefits could be obtained from ewe's milk fat product consumption.…”
Section: Mutfa Content and Profilementioning
confidence: 86%
“…Recent studies [10] have found that most of the RA in ruminant milk fat is synthesized endogenously from 11-trans C18:1 by desaturases. Furthermore, TVA has also been found as an RA precursor in human tissues [28]. If this evidence were confirmed, remarkable benefits could be obtained from ewe's milk fat product consumption.…”
Section: Mutfa Content and Profilementioning
confidence: 86%
“…The observed increase in the content of trans-18:1 isomers when supplementing with oils rich in oleic acid could be due to the fact that oleic acid can interfere with the biohydrogenation of linoleic acid, leading to an accumulation of trans-18:1 (Mosley et al, 2002). Due to the ability of Δ 9 desaturase in human tissue to transform t 11-18:1 into c 9,t 11-18:2 (Turpeinen et al, 2002), the increase in the t 11-18:1 content in meat implies an improvement of its lipid profile.…”
Section: Meat Qualitymentioning
confidence: 99%
“…However, this could be ascribed to the fact that R-TFA generally is consumed (1) in much lower quantities than IP-TFA and (2) together with dairy products, which may be heart protective (Warensjo et al, 2010). Alternatively, the weak tendency for a risk reduction seen with R-TFA, may relate to the fact that vaccenic acid may be converted endogenously to the conjugated linoleic acid isomer c9,t11-18:2 (Turpeinen et al, 2002), the adipose tissue content of which has been shown to be inversely associated with myocardial infarction risk (Smit et al, 2010).…”
Section: Nhsmentioning
confidence: 99%